2019
DOI: 10.1371/journal.pone.0213227
|View full text |Cite
|
Sign up to set email alerts
|

Flooding and hydrologic connectivity modulate community assembly in a dynamic river-floodplain ecosystem

Abstract: Braided river floodplains are highly dynamic ecosystems, where aquatic communities are strongly regulated by the hydrologic regime. So far, however, understanding of how flow variation influences assembly mechanisms remains limited. We collected benthic chironomids and oligochaetes over a year across a lateral connectivity gradient in the semi-natural Tagliamento River (Italy). Four bankfull flood events occurred during the study, allowing the assessment of how flooding and hydrologic connectivity mediate the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 80 publications
(165 reference statements)
0
25
0
Order By: Relevance
“…Fish species are able to shift their diet according to changes in resource availability (Goulding 1980;Hahn et al, 1997;Agostinho et al, 2007). In river floodplains, resource abundances are regulated by spatial and temporal variations in environmental conditions due to variations in forest cover and seasonal hydrological changes in the lateral extent of the river channel (Junk and Wantzen, 2004;Arantes et al, 2019;Larsen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fish species are able to shift their diet according to changes in resource availability (Goulding 1980;Hahn et al, 1997;Agostinho et al, 2007). In river floodplains, resource abundances are regulated by spatial and temporal variations in environmental conditions due to variations in forest cover and seasonal hydrological changes in the lateral extent of the river channel (Junk and Wantzen, 2004;Arantes et al, 2019;Larsen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the floodplains are isolated from river mainstream at low flow when most studies are conducted, and the concept of the connectivity is not well defined. In fact, aquatic communities in floodplain waterbodies are not only influenced by the environmental variation that is observed at low flow; they are also strongly influenced by the hydrological and biological processes during flood and flood recession periods (Larsen et al, 2019;Thomaz et al, 2007). For example, flow pulses may differently modify the physical and chemical environment of each waterbody, thereby altering the suitability of habitats for aquatic organisms over time and space (Tockner et al, 2000;Ward et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, some studies found that temperate communities were more environmentally controlled than tropical ones, which were more spatially structured (Myers et al 2013; Souffreau et al 2015). In addition, massive floods during the rainy season increase the aquatic connectivity in the tropical regions (Junk et al 1989; Bunn et al 2006; Larsen et al 2019), reducing dispersal limitation and homogenizing local communities (Thomaz et al 2007; Brasil et al 2020), and contrasting with the more intense isolation of the Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%